Pemenuhan Hak Atas Pendidikan (Dasar) bagi Komunitas Adat Terpencil di Perbatasan antar Negara (Studi Kasus di Provinsi Kalimantan Barat, Nusa Tenggara Timur) - Rully Rachman (Jurnal HAM, 2012)
The Indonesian Government still has limitations in handling areas that are geographically difficult to reach. In such a circumstance, there are several remote areas that are inhabited by Indonesia citizens in the form of indigenous communities who are isolated from other residents in the vicinity.Article 28 C Paragraph (1) of the Constitution of the Republic of Indonesia Year 1945 states that "every person has the right to develop themselves through the fulfillment of basic needs, right to education, and to benefit from science and technology, art and culture, in order to improve the quality of life and for the welfare of mankind". Consequently, education and compliance services shall also cover remote indigenous communities. This statement would be in line with Article 12 of Law Number 39 Year 1999 on Human Rights, which states that "everyone is entitled to protection of personal development, to education, educating themselves, and improve the quality of life for a man who is faithful, pious, noble responsibility, and prosper in accordance with human rights".The study uses a qualitative descriptive research with case studies. The samples are SDN 03 and SDN Sontas 12 Entikong in the province of West Kalimantan, and SDN Nanaeklot in East Nusa Tenggara Province.